2015
DOI: 10.1002/bip.22744
|View full text |Cite
|
Sign up to set email alerts
|

Review structure‐ and dynamics‐based computational design of anticancer drugs

Abstract: Cancer is a class of highly complex diseases involving multiple genes and multiple cross-talks between signaling networks. Cancer cells may be developed from inherited defects or acquired damages of DNA. However, many cancers are resistant to treatment, and metastasis of cancers makes the disease even more intractable. Secondary malignancies are frequently observed after cancer chemotherapy. The call for more effective cancer therapy is obligatory. Using drug-cocktails that combine multiple anti-cancer agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 114 publications
(159 reference statements)
0
7
0
Order By: Relevance
“…Finally, recent pharmacology research has revealed the necessity to design compounds that act on multiple genes or molecular pathways. [14][15][16][17] In our study, we identified compounds targeting the differentiation of LUAD phenotypes, which may provide therapeutic targets for further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent pharmacology research has revealed the necessity to design compounds that act on multiple genes or molecular pathways. [14][15][16][17] In our study, we identified compounds targeting the differentiation of LUAD phenotypes, which may provide therapeutic targets for further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The methods that are used in this research have been used intensively in drug design (Hellberg et al, 1987;Wishart et al, 2006;Matta & Boyd, 2007;Yuan et al, 2013;Distinto et al, 2015;Kristensen et al, 2015;Lin, 2016;Wang et al, 2016;Xiao et al, 2016), and it is hoped that their use in this field complements the experimental information from a new approach, favouring the holistic comprehension of the phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary malignancies are the cancers occurring even after the initial treatment of the primary cancer. Radiotherapy with or without chemotherapy is a potential risk factor for secondary malignancies (Lin, 2016). Though ionizing radiations are used to destroy cancerous tissues, the incidence of second malignant neoplasm (SMN) arises among long-term survivors.…”
Section: Secondary Malignancies After Radiation Therapymentioning
confidence: 99%